Weaning stress and gastrointestinal barrier development: Implications for lifelong gut health in pigs - Moeser, Adam J. (Anim Nutr, 2017)
The gastrointestinal (GI) barrier serves a critical role in survival and overall health of animals and humans. Several layers of barrier defense mechanisms are provided by the epithelial, immune and enteric nervous systems. Together they act in concert to control normal gut functions (e.g., digestion, absorption, secretion, immunity, etc.) whereas at the same time provide a barrier from the hostile conditions in the luminal environment. Breakdown of these critical GI functions is a central pathophysiological mechanism in the most serious GI disorders in pigs. This review will focus on the development and functional properties of the GI barrier in pigs and how common early life production stressors, such as weaning, can alter immediate and long-term barrier function and disease susceptibility. Specific stress-related pathophysiological mechanisms responsible for driving GI barrier dysfunction induced by weaning and the implications to animal health and performance will be discussed.